LAYANAN BIMBINGAN KELOMPOK PADA SISWA MI MUSLIMIN YANG MEMILIKI KEPERCAYAAN DIRI RENDAH - Pipih Ratna Puri; Asep Samsudin; Riesa Rismawati Siddik (IKIP Siliwangi, 2021)
The purpose of this study is to determine group guidance services in increasing student self-confidence. This research method uses literature review method from previous research. The subjects of this study are some of the results of previous research which are in accordance with the variables discussed in this research. From the results of research group guidance services can be used as an effort to increase student self-confidence, this is evidenced by a change in the subject after the implementation of group guidance (previous literature review). Based on the results of the study that had been done, it was found that through the group guidance technique the students' self-confidence began to build. This can be seen from the increased students' understanding of the rules in life and increased confidence in themselves regarding the ways that can be done in solving each problem. The conclusion of this study is that group guidance services can be used to increase students' self-confid Keywords: group guidance, self-confidence